2015
DOI: 10.1111/nph.13606
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy responses to temperature relate toNothofagusspecies distribution and determine temporal patterns of germination across altitudes in Patagonia

Abstract: Summary Seeds integrate environmental cues that modulate their dormancy and germination. Although many mechanisms have been identified in laboratory experiments, their contribution to germination dynamics in existing communities and their involvement in defining species habitats remain elusive. By coupling mathematical models with ecological data we investigated the contribution of seed temperature responses to the dynamics of germination of three Nothofagus species that are sharply distributed across differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 46 publications
1
33
1
2
Order By: Relevance
“…The germination rate (GR) has commonly been used to obtain the germination limits of seeds of several species (Covell et al, 1986;Bradford, 2002;Arana et al, 2016;Seal et al, 2017Seal et al, , 2018Castillo-Lorenzo et al, 2019) due to its linear relation with temperature (Covell et al, 1986). On account of that, the temperature limits, as well as the sub-and supraoptimum thermal times (Figure 4) could be calculated for germination of M. urundeuva seeds.…”
Section: Effects Of the Environmental Stress On Germinationmentioning
confidence: 99%
“…The germination rate (GR) has commonly been used to obtain the germination limits of seeds of several species (Covell et al, 1986;Bradford, 2002;Arana et al, 2016;Seal et al, 2017Seal et al, , 2018Castillo-Lorenzo et al, 2019) due to its linear relation with temperature (Covell et al, 1986). On account of that, the temperature limits, as well as the sub-and supraoptimum thermal times (Figure 4) could be calculated for germination of M. urundeuva seeds.…”
Section: Effects Of the Environmental Stress On Germinationmentioning
confidence: 99%
“…Among the endogenous factors, several studies have shown that seed germination is genetically determined and the phylogenetic signal may be a significant constraint to interspecific variation within a genus (Zhang, Du, & Chen, 2004). This was found, for example, for some Romulea species in Mediterranean habitats (Carta, Hanson, & Müller, 2016), even though a contrasting behavior was observed with other genera, such as Stellaria and Nothofagus, which showed considerable interspecific variability in germination behavior (Arana et al, 2016;Vandelook, Van de Moer, & Van Assche, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…European beech (Fagus sylvatica L.) is an example of an expansive tree species, and ongoing changes in climate conditions could expand its potential range. Beech stand vitality is high, and its regeneration is well adapted to different site conditions at the limit of the species' distribution; thus, European beech will probably reach its northeastern limit in the future [143].…”
Section: Climate Is An Important Selective Factor In Populationsmentioning
confidence: 99%